STRONGER HANDS, STRONGER BLADDERS: UNCOVERING THE CONNECTION BETWEEN HANDGRIP STRENGTH AND URINARY INCONTINENCE IN ELDERLY WOMEN - Setiawan, Fiona Valencia; Dewi, Andriana Kumala; Firmansyah, Yohanes; Sari, Triyana; Santoso, Alexander Halim (Prosiding Seminar Nasional COSMIC Kedokteran, 2025)
Urinary incontinence (UI) is a prevalent issue among elderly women, significantly impacting their quality of life. Handgrip strength, an indicator of overall muscle strength, is understudied in its role concerning UI. Utilizing handgrip strength to measure overall muscle strength, including pelvic floor muscles, introduces a novel approach to supporting continence maintenance in elderly women. The aim is to determine the correlation between handgrip strength and UI severity among elderly women, using the International Consultation on Incontinence – Short Form (ICIQ-SF) for measurement. This study involved 74 elderly female participants at Bina Bhakti Nursing Home. Spearman’s correlation was employed to analyze the relationship between handgrip strength (in kilograms), measured with the Omron Handgrip Strength device on the right hand, and UI severity was assessed through the ICIQ-SF scoring questionnaire, with scores ranging from 0 to 21. Findings indicated a statistically significant negative correlation between handgrip strength and UI severity (r = -0.245, p = 0.035). This suggests that higher handgrip strength correlates with lower UI severity. The study found a significant correlation between handgrip strength and UI in elderly women, indicating that strength-building interventions may reduce UI severity.